2012
DOI: 10.1159/000339175
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of the Effects of Telmisartan on Angiotensin II-Induced Mechanical Changes in Live Mesangial Cells Using Atomic Force Microscopy

Abstract: Background/Aims: Recent studies have shown that angiotensin II (Ang II) type 1 receptor blockers (ARB) may provide renal protection independent of their blood pressure-lowering effect. However, evidence for this comes from indirect methods, such as genetic or protein expression studies. In this study, we hypothesized that telmisartan, a specific ARB, applied to Ang II-stimulated mesangial cell (MC) would exert a renoprotective effect via modulation of MCs’ mechanical properties. Methods: We investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…More recently, with some modification to their general setup, AFMs have also been used to resolve point forces exerted at the cell surface by attaching the tip of the AFM to the cell membrane, and then measuring the deflection of the cantilever arm due to contraction, migration, and other cellular events. In this configuration, AFMs have been used to measure forces at cell-ECM junctions [149][150][151][152], tugging forces at cell-cell interfaces [153,154], protrusive forces at the lamellipodia of a migrating cell [123,[155][156][157], changes to cell forces upon chemical treatment [158], cell contractile forces [159], and the electrical activity of stimulated cells [160]. AFMs are sophisticated tools that can resolve piconewton forces and interrogate nanoscale structures of a cell.…”
Section: -4 / Vol 65 November 2013mentioning
confidence: 99%
“…More recently, with some modification to their general setup, AFMs have also been used to resolve point forces exerted at the cell surface by attaching the tip of the AFM to the cell membrane, and then measuring the deflection of the cantilever arm due to contraction, migration, and other cellular events. In this configuration, AFMs have been used to measure forces at cell-ECM junctions [149][150][151][152], tugging forces at cell-cell interfaces [153,154], protrusive forces at the lamellipodia of a migrating cell [123,[155][156][157], changes to cell forces upon chemical treatment [158], cell contractile forces [159], and the electrical activity of stimulated cells [160]. AFMs are sophisticated tools that can resolve piconewton forces and interrogate nanoscale structures of a cell.…”
Section: -4 / Vol 65 November 2013mentioning
confidence: 99%
“…The main finding of our study was the observation of an inhibition of the contractile response to Ang II in mesangial cells pre-treated with telmisartan, which was associated with alterations in cell stiffness15). We also demonstrated that telmisartan-pretreated cells showed smaller pull-off forces than did the mesangial cells before treatment15). Measuring the stiffness and adhesive properties of mesangial cells after telmisartan treatment allowed us to explore the roles of Ang II receptor blocker in structural and dynamic changes of mesangial cells.…”
Section: A New Technical Approach To Monitor the Effects Of Anti-hypementioning
confidence: 58%
“…We demonstrated for the first time the use of AFM force-distance curves on live mesangial cells to directly monitor changes in surface adhesion and stiffness of cells upon treatment with telmisartan in real time15). The main finding of our study was the observation of an inhibition of the contractile response to Ang II in mesangial cells pre-treated with telmisartan, which was associated with alterations in cell stiffness15). We also demonstrated that telmisartan-pretreated cells showed smaller pull-off forces than did the mesangial cells before treatment15).…”
Section: A New Technical Approach To Monitor the Effects Of Anti-hypementioning
confidence: 99%
“…Recently, many studies suggested that the information obtained via AFM helps in understanding the biological and physical mechanism of renal injury [ 17 , 18 ]. Our group previously used AFM to monitor Ang II-induced conformational changes in mesangial cells [ 19 ], and we also successfully observed that the changes in the Ang II-stimulated mesangial cells were effectively disrupted by treatment with telmisartan, a specific AT 1 receptor blocker [ 20 ]. However, only a few studies investigated the changes of TECs using AFM.…”
Section: Introductionmentioning
confidence: 99%